Adherence to lifestyle interventions and its effect on metabolic and behavioral outcomes in type 2 diabetes mellitus cases - Khalid-Al-Azam, M.; Sarkar, Swapan Kumar; Hasan, S. M. Mahmudul (International Journal Of Community Medicine And Public Health, 2025)
Background: Type 2 diabetes mellitus (T2DM) is a major global health concern, often exacerbated by sedentary lifestyles and poor dietary habits. Lifestyle interventions, including dietary modifications, physical activity, and behavioral changes, are essential for managing T2DM. However, adherence to these interventions is a significant challenge. Methods: This cross-sectional observational study was conducted over six months, from July to December 2023, in Rajapur Upazila of Jhalokathi district and Bhandaria Upazila of Pirojpur district under the guidance of the Department of Biomedical Engineering and Public Health, World University of Bangladesh. This study evaluated the effectiveness of a structured non-pharmacological lifestyle intervention on metabolic parameters in individuals with T2DM. The primary outcomes measured were HbA1c, fasting blood glucose, and body mass index (BMI). Results: Of 150 patients, 124 (82.67%) were uncontrolled (FBS>6.4), and 26 (17.33%) were controlled (FBS <6.4). Most patients (77.33%) had a BMI of 20-29, with a mean BMI of 22.46±3.39 (p<0.001). Hypertension was present in 39 (26%) patients. In group A1 (<50 years, non-pharmacological intervention), post-intervention results showed FBS 6.32±0.72 mmol/l (p<0.001), HbA1c 6.72±0.41% (p<0.001). In group A2 (>50 years, combined intervention), FBS decreased to 6.47±1.00 mmol/l (p<0.001) and HbA1c to 6.86±0.56% (p=0.004). Conclusions: Non-pharmacological interventions focusing on lifestyle changes can result in meaningful improvements in metabolic control for individuals with T2DM. Enhancing adherence remains a key challenge for maximizing long-term benefits.